The Effect of Managerial Ownership and Institutional Ownership on Company Value in Mining Companies Listed on the Indonesia Stock Exchange - Muhammad Rafsanjani; Isnurhadi Isnurhadi; Marlina Widiyanti; Kemas Muhammad Husni Thamrin (Publikasi Indonesia, 2024)
This study aims to examine the influence of managerial ownership and institutional ownership on company value as an intervening variable in mining companies listed on the Indonesia Stock Exchange. The data used is secondary data obtained from the annual reports of mining companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The analysis method used is multiple linear regression with the help of SPSS software. The results of the study show that managerial ownership has a significant positive effect on the company's value. Likewise, institutional ownership has a significant positive effect on the value of the company. As an intervening variable, it has also been proven to affect the relationship between managerial ownership, institutional ownership, and company value. The Adjusted R Square in this study is 0.309, which means that 30.9% of the variation in the value of the company can be explained by the variables of managerial ownership and institutional ownership, while the remaining 69.1% is explained by other factors that were not studied in this study.